Literasi Kewarganegaraan Sebagai Strategi Dalam Mengembangkan Civic Knowledge - Lambertus Kollo , Fredik; Tapatab, Shintya M.; Famau, Wempi W.; Nua Oba, Petrus F. (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2024)
Civic literacy is the initial ability of every citizen in developing knowledge, skills and attitudes. The purpose of this writing is to find out the strengthening of civic literacy as a strategy in developing civic knowledge. The method in writing this scientific paper is the literature review method. The results of this study found that literacy as the initial ability of citizens has an important role in developing knowledge, skills and attitudes. This research specifically examines literacy as a strategy in developing civic knowledge. Citizens have the initial ability of literacy in order to become smart citizens and be able to develop their rights and obligations as citizens.